Gambaran Loneliness terhadap Lansia yang Mengalami Kedukaan pada Masa Pandemi Covid-19 di Denpasar, Bali - Gusti Ayu Gita Ananda Murni; Agnes Utari Hanum Ayuningtias; Tio Rosalina (Universitas Kristen Maranatha, 2022)
This study aims to discover in depth the description of loneliness in the elderly of Balinese ethnicity who experiences grief for life partners and how the feelings of loneliness are felt by individuals when experiencing grief events in their lives. The study uses a qualitative method. The approach used in this study is phenomenology with the elderly subject of Balinese ethnicity, who experienced grief events due to being left by their life partner, located in Bali. The data collection method used is by interviewing the subject and informant. The forms of data analysis used are data reduction, data interpretation, data categorization, and data grouping according to themes, and making narratives from the results obtained. The results obtained from this study are the feeling of the loneliness felt by the elderly due to different grief events. This result can influence by internal (individual) factors such as emotions, the individual's personal and external (social) aspects, such as family, friends, neighbors, and the shape of the house, both of which have a very important role in shaping the feeling of loneliness in the elderly who experience grief. It can conclude that the feeling of loneliness that can be felt by the elderly depends on how the elderly respond to the grief event.